Methodological proposal: integration of information and communication technologies to the educommunication process - León-Martínez, Fredy; León-Martínez, Fernando; Guillermo-Ríos, Víctor (Revista revoluciones, 2021)
The purpose was to diagnose the equipment and the use of ICTs in the teaching and learning process in teachers and students of the Information Sciences and Social Communication Career of the Catholic University of Cuenta (Ecuador). The research approach used was qualitative-quantitative, descriptive and cross-sectional. The sample population consisted of 10 teachers (between 40 and 53 years old) and 103 students from the first to the tenth cycle (between 17 and 36 years old). The instruments for obtaining data was the closed questionnaire established on the Likert scale and as a complement it was the observation guide, both structured in three components: 1) Structure and use of technology. 2) Perceptions on the use of technological tools and 3) Technological equipment, their obtaining of information was generated based on a bibliographic tracking and analysis in academic search engines, magazines, conferences and seminars; as well as in scientific databases, which allowed to provide an analysis of the essential elements for the study of research, where it is determined that students have a greater use of communication technologies in relation to that of their teachers, since that students, being in a millennial system, have better knowledge and skills, since in their generation of the eighties they have an act of technological knowledge, social and ethical values.